Reprogramming metabolic pathways in vivo with CRISPR/Cas9 genome editing to treat hereditary tyrosinaemia - Francis P. Pankowicz (Nature Portfolio, 2016)
Hereditary tyrosinaemia type I is caused by a gene defect that leads to a lethal accumulation of toxic metabolites in the liver. Here the authors use CRISPR/Cas9 to 'cure' the disease in mice by inactivating another gene, rather than targeting the disease-causing gene itself, to reroute hepatic tyrosine catabolism.